2023
DOI: 10.1108/jarhe-08-2022-0273
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the perceptions and experiences of university lecturers on corrective feedback in students' research project supervision: a case for computer-mediated mode

Abstract: PurposeThis study intends to add to the existing body of literature and provides a strong advocacy for the use of the computer-mediated corrective feedback by university lecturers in Nigeria and elsewhere. The purpose of this paper is to explore the perceptions and experiences of lecturers toward students' research project supervision using the computer-mediated corrective feedback, factors that facilitate its use, the most preferred computer-mediated corrective feedback types and the extent of its usage in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
0
0
Order By: Relevance
“…also present a correlation between bullying and dropping out of school, particularly for bullies. Osiesi et al (2023) confirmed the links between bullying and dropping out of school made by when discussing the problem of dropping out among primary school children in Etiki State, Nigeria. The research concurs that school bullying always leads to decreased participation in school activities and dropping out.…”
Section: Effect Of Bullying On Academic Achievementsupporting
confidence: 55%
“…also present a correlation between bullying and dropping out of school, particularly for bullies. Osiesi et al (2023) confirmed the links between bullying and dropping out of school made by when discussing the problem of dropping out among primary school children in Etiki State, Nigeria. The research concurs that school bullying always leads to decreased participation in school activities and dropping out.…”
Section: Effect Of Bullying On Academic Achievementsupporting
confidence: 55%